Rekayasa Model Perencanaan Transportasi dalam Menciptakan Mobilitas yang Aman pada Masa Pandemi Covid 19 (Studi Kasus : Mobilitas Mahasiswa di Jawa Timur) - Alfiatus Aisyah Nurhidayah; Amanda Ristriana Pattisinai (UM Purwokerto Press, 2021)
The mobility restriction policy imposed in response to the increasing transmission of Covid-19 brought changes in people's travel behavior, both at the global and local levels. The four traditional models at the transportation planning stage became biased because the need for travel was different during this pandemic. This study aimed to create a modification of transportation planning, where the mobility continues to use the existing four-stage transportation planning model but at the same time ensures safety from the dangers of Covid-19 transmission. The survey was conducted online on students (N=100) spread across cities in East Java Province, where the impact of the COVID-19 pandemic in the implementation of higher education, especially student mobility. The research findings indicated that students still travel actively to universities. The student's motive for traveling was only because of important and urgent matters dominated by work and receiving news of death from family. In contrast, the majority used private vehicles, especially on trips within the city. However, the tendency to use public transportation when traveling long distances was also still in demand by respondents.